POTENTIALS OF POLYACRYLAMIDE-SODIUM CARBOXYMETHYL CELLUOSE GRAFT POLYMER AS FLOODING MATERIAL IN ENHANCED CRUDE OIL RECOVERY (Biological Sciences - PJSIR, 2002)
Celluose-based derivatives have been used in drilling fluids  as viscosifiers  and  fluid loss  reducers  for many  years.  But  more recently due to evident advantages, such as technology and relative ease of large-scale production of  cellulose  derivatives as powders or granules and the generally non-toxic nature of cellulose ethers, research efforts  have  been  intensified to optimize their possible applications as polymer  flooding materials  in  enhanced  oil recovery.  Consequently, this paper addresses the synthesis and characterization of polyacrylamide-sodium carboxymethyl cellulose graft polymer produced  from  locally  available  cellulose material.Notable improvement was achieved in the specific viscosity of he graft polymer  when  compared  with  the  unmodified sodium carboxymethyl cellulose (NaCMC). For a I% (wt%) solution at 25°C and a shear rate of 200s·1, NaCMC has a viscosity of 74.6 centipose while the graft polymer recorded a viscosity of 154 centipose. The influence of mono and multivalent cations such as sodium, calcium and alumunium ions on the viscosity of  the  graft  polymer  solution  was relatively  minimal,  suggesting  improvement  in the  so-called  salt tolerance  or cation  compatibility .